The Effect of Semen Storage Temperature and Diluent Type on the Sperm Quality Index of Broiler Breeder Semen - Dumpala, P.R.; Parker, H.M.; Mc Daniel, C.D. (International Journal of Poultry Science, 2006)
The sperm quality index (SQI) is predictive of fresh semen quality. Our objective was to examine if semen storage affects the SQI obtained from undiluted semen, or semen diluted with either Beltsville Poultry Semen Extender (BPSE) or Minimum Essential Medium (MEM) and held for 8 h at 4, 21, or 41oC. Dead sperm percentage was higher and SQI was lower from undiluted versus diluted semen. Dead sperm percentage was higher and SQI was lower for semen stored at 41oC than at lower temperatures. Overall, there was a linear increase in dead sperm percentage and linear decrease in SQI over storage length. Regardless of diluent, there was a linear increase in dead sperm percentage over time for semen stored at 4 and 21oC. For semen held at 41oC and diluted with BPSE or MEM there were respective quartic and linear increases in dead sperm percentage over time; a drastic linear increase existed for undiluted semen. There was a linear decrease in SQI from undiluted semen and semen diluted with MEM over time at 4oC; however, for semen diluted with BPSE, there was a linear increase. The SQI from undiluted semen stored at 41oC decreased linearly over time. At 41oC, a cubic relationship existed for SQI over time for semen diluted with BPSE, and a linear decline was detected for semen diluted with MEM. In conclusion, the SQI is indicative of changes induced by diluent type, storage temperature, and length of semen storage.